The Immunology of Delirium - Cerejeira, J (2014)
Delirium is an acute neuropsychiatric syndrome characterized by acute-onset global cognitive deficits, perceptual and behavioural disturbances affecting mainly elderly subjects with underlying medical or surgical conditions. The pathophysiology of delirium is complex and inflammation is a relevant precipitant factor of this syndrome, although it remains unclear how acute systemic inflammation induces the clinical picture of delirium. The central nervous system is able to detect peripheral infection or tissue destruction through circulating immune mediators and neural ascending signs. Activated microglia is responsible for an acute neuroinflammatory reaction underlying the symptoms of sickness. In healthy conditions descending pathways from the paraventricular nucleus, locus coeruleus and dorsal motor nucleus organize a centralized response to influence the immune response at the periphery and restore homeostasis. In the context of ageing and chronic neurodegeneration, adaptive changes to acute insults are characterized by exaggerated production of pro-inflammatory cytokines by primed microglia coupled with dysfunction of brain-to-immune pathways. In animal models, these changes underlie a more severe manifestation of sickness behaviour with working memory deficits suggesting that inattention, a core feature of delirium, can be a clinical correlate of an increased neuroinflammatory reaction. In patients with delirium, higher levels of pro-inflammatory cytokines and cortisol were identified in plasma and cerebrospinal fluid. However, to date it has not been clarified how peripheral inflammatory or endocrine biomarkers can reflect the likelihood or severity of delirium symptoms. In the future, a better understanding of the interaction between the brain and peripheral organs and the exact mechanism by which systemic inflammation can lead to delirium, will allow the development of new therapeutic agents.